Adverse Impact of Rheumatoid Arthritis on Pregnancy Outcomes: A Saudi Arabia Prospective Multicenter Study - Al Rayes H (Dove Medical Press, 2021)
Hanan Al Rayes,1 Sultana Abdulaziz,2 Asma Mohammed Alotaibi,3 Mufaddal Adil Alaithan,1 Mohammed Attar,4 Hassan Daghasi,4 Rand Melibari,2 Ali H Althagafi,4 Basant Elnady4,5 1Rheumatology Division, Department of Medicine, Prince Sultan Military Medical City, Riyadh, Saudi Arabia; 2Division of Rheumatology, Department of Medicine, King Fahad Hospital, Jeddah, Saudi Arabia; 3Department of Medicine, Prince Sultan Military Medical City, Riyadh, Saudi Arabia; 4Division of Rheumatology, Department of Medicine, Al Hada Armed Forces Hospital, Taif, Saudi Arabia; 5Rheumatology, Rehabilitation and Physical Medicine Department, Faculty of Medicine, Benha University, Benha, EgyptCorrespondence: Basant ElnadyDivision of Rheumatology, Department of Medicine, Al Hada Armed Forces Hospital, Al Hada Ring Road, Al Hada, Postal Code 1347, Taif, Zip Code 21944, Saudi ArabiaTel +966562387723Fax +966127542811Email basantelnady@gmail.comBackground: Rheumatoid arthritis (RA) is associated with adverse pregnancy outcomes and postpartum complications, especially with severe disease activity.Objective: The current study aimed to compare the pregnancy outcomes in patients with RA and healthy controls as well as to assess the impact of disease-related variables, medications and disease activity on pregnancy and neonatal-related outcomes in the Saudi population.Methods: This prospective multicenter study included pregnant female patients with RA from three tertiary centers in Saudi Arabia. The demographics, disease activity scoring (DAS28-CRP), medication before and during pregnancy, pregnancy-related outcomes, and complications in comparison to age-matched healthy female controls were noted.Results: A total of 77 pregnant patients with RA and 250 healthy age-matched pregnant controls were included in the study. A total of 67.53% were in remission before conception (DAS28CRP ≤ 2.6), and 81.8% of pregnancies were planned. Age of conception, preterm labor, neonatal intensive care unit (NICU) admission and low birth weight were statistically significant (p < 0.05) and higher in RA patients than in healthy controls. Longer disease duration (p < 0.001), and high C-reactive protein and erythrocyte sedimentation rate levels before conception (p ≤ 0.001) were statistically associated with preterm NICU admission. There was statistically significant association between mild (p = 0.015) or moderate to severe DAS28-CRP (p = 0.001) and RA patients regarding pregnancy outcomes. The classification table obtained from the logistic model showed patients with mild and moderate-severe DAS28-CRP have significantly high chances of having an adverse pregnancy outcome.Conclusion: RA has a negative impact on pregnancy-related outcomes. Higher disease activity is considered a major risk; thus, tight disease control should be aimed. Planned pregnancy follow-up is associated with better pregnancy outcomes.Keywords: rheumatoid arthritis, pregnancy, disease activity